2019
DOI: 10.3390/molecules24173205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorogenic Acid on the Physicochemical and Functional Properties of Coregonus Peled Myofibrillar Protein through Hydroxyl Radical Oxidation

Abstract: The effects of chlorogenic acid (CA) (6, 30, and 150 μM/g protein) on the physicochemical and functional properties of Coregonus peled myofibrillar protein (MP) through oxidation using a hydroxyl radical oxidation system (0.01 mM FeCl3, 0.01 mM Asc, and 1 mM H2O2) were investigated. The result showed that CA inhibited the increase in protein carbonyl content but did not prevent losses in sulfhydryl and free amine contents caused by oxidation. The presence of CA also increased conformational changes in the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In vitro experiments show the conjugate based hydrogels can be adsorbed onto the outer membrane of mesenchymal stem cells and further induce osteoblastogenesis upon stem cells. Interestingly, Guo et al 93 recently demonstrated the gel property of chlorogenic acid-myobrillar protein conjugates is closely related to the amount of phenolics covalently linked. The conjugates with high conjugation efficiency can cause excessive aggregate formation and possibly shield functional groups involved in gel formation, thereby producing a poor gel network.…”
Section: Hydrogels and Nanoparticles For Controlled Drug Releasementioning
confidence: 99%
“…In vitro experiments show the conjugate based hydrogels can be adsorbed onto the outer membrane of mesenchymal stem cells and further induce osteoblastogenesis upon stem cells. Interestingly, Guo et al 93 recently demonstrated the gel property of chlorogenic acid-myobrillar protein conjugates is closely related to the amount of phenolics covalently linked. The conjugates with high conjugation efficiency can cause excessive aggregate formation and possibly shield functional groups involved in gel formation, thereby producing a poor gel network.…”
Section: Hydrogels and Nanoparticles For Controlled Drug Releasementioning
confidence: 99%
“…Modications of protein or peptide with hydroxyl radicals (OHc) generated from redox reaction caused increasing intensities of the amide peaks. 31,32 Also, the shi to a lower wavenumber of amide II (1546 cm À1 to 1541 cm À1 ) and amide III (1254 cm À1 to 1209 cm À1 ) observed (Fig. 3a) in OHC sample might be related to interaction between OHc radical and peptides of HC via covalent bond, especially at N-H groups of peptides.…”
Section: Resultsmentioning
confidence: 90%
“…As depicted in Table 1, the free amino groups of oxidized WPI decreased with the AAPH concentration, and the minimum (0.31 nmol/mg) was discerned at a concentration of 10 mmol/L, which could be due to the oxidation of amino-containing side chain (threonine, proline, arginine and lysine residues) in WPI [29], and the formation of Schiff base with carbonyl groups by a covalent reaction [19]. This finding echoed that of the carbonyl result mentioned above and a similar result was obtained with oxidized Coregonus peled myofibrillar proteins [29].…”
Section: Free Amino Groupsmentioning
confidence: 99%
“…The absorbance at 340 nm was measured against distilled water as control. This trial was repeated three times to calculate the free amino group content [19].…”
Section: Determination Of Free Amino Groups Contentmentioning
confidence: 99%